From Crisis Narratives about Political Parties to Observing Practices of Exclusion. A Programmatic Introduction. - Dobusch, Laura; Kreissl, Katharina; Siri, Jasmin (Momentum Quarterly, 2013)
Word of the ever more intensifying crisis of political parties is regarded as common sense in the public and scientific discourse. However, a glance cast at history shows that crisis narratives are not a new phenomenon, they rather accompany the parties since their founding. This is owed to the fact that parties are measured according to their ideal democratic conceptions to which they inevitably fail, due to their organizational character. Thus it is even more necessary to take a look at parties from an organizational-theoretical perspective and to question them according to their internal procedures, programs and member roles. Against this background, we sketch current inclusive and exclusive practices developed by German parties and examine which persons or groups experience particular privileges or marginalization in this respect. Beyond ideological frontiers we ask how parties can turn into „inclusive organizations“. Please find enclosed the description of each article in this Special Issue, all applying an empirical perspective on parties apart from the convential crisis diagnosis
Keywords: political parties; organization; crisis; exclusion; inclusion; democracy; quota regulation